3de Kulturele Manifestatie Watersportbaan Gent. - Neirynck, Freek; Raes, Godfried Willem; Schepens, Herman; Temmerman, Jan; Van Gysegem, Paul (Gent : C.S.C. "Hardijns", 1983)
Cauwelier, Willy ; Cauwenberghs, Luc ; Clemencon, Jean-Pierre ; Coenen, Jean ; De Blok, Luc ; De Clercq, Rosita ; Decq, Bart ; De Deken, Jean ; De Middeleer, Dirk ; Desmet, Etienne ; Feulien, Marc ; Flips, Georges ; Ganzevoort, Wijbrandt ; Gaube, Bernard ; Haenen, Toon ; Han, Deij ; Huylebroeck, Paul ; Meier, Gaby ; Mouton, Jef ; Moving, Mass and Individual ; Perneel, Paul ; Sleppe ; Thiran, Bernard ; Dumont, Paul ; Van den Abbeel, Jan ; Van Elslande, Rudy ; Van Gysegem, Paul ; Van Rafelghem, Paul ; Vastesaeger, Ludo ; Vercaemer, Geert ; Walraevens, Frans
biografie
3de Kulturele Manifestatie Watersportbaan Gent, 3.9. - 1.10.1983
Nederlands
boek